2006
DOI: 10.1002/art.22204
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, prospective, randomized, double‐blind, placebo‐controlled trial of corticosteroids and intravenous cyclophosphamide followed by oral azathioprine for the treatment of pulmonary fibrosis in scleroderma

Abstract: Objective. The lack of randomized controlled trials (RCTs) in pulmonary fibrosis in systemic sclerosis (SSc) has hampered an evidence-based approach to treatment. This RCT was undertaken to investigate the effects of intravenous (IV) cyclophosphamide (CYC) followed by azathioprine (AZA) treatment in pulmonary fibrosis in SSc.Methods. Forty-five patients were randomized to receive low-dose prednisolone and 6 infusions (monthly) of CYC followed by oral AZA, or placebo. Primary outcome measures were change in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
396
1
42

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(445 citation statements)
references
References 30 publications
6
396
1
42
Order By: Relevance
“…While these beneficial effects were wide-ranging, the overall magnitude of change in FVC was small and dissipated by the end of 24-months (3-4). A small but beneficial effect of intravenous CYC on lung function was also suggested by the Fibrosing Alveolitis in Scleroderma Trial (2). Based on these studies and the known side effects of CYC, some investigators have concluded that the potential risks from CYC outweigh the benefits (5,(7)(8).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While these beneficial effects were wide-ranging, the overall magnitude of change in FVC was small and dissipated by the end of 24-months (3-4). A small but beneficial effect of intravenous CYC on lung function was also suggested by the Fibrosing Alveolitis in Scleroderma Trial (2). Based on these studies and the known side effects of CYC, some investigators have concluded that the potential risks from CYC outweigh the benefits (5,(7)(8).…”
Section: Discussionmentioning
confidence: 98%
“…At present, only daily oral or pulse intravenous cyclophosphamide (CYC) have been shown in large randomized, doubleblinded, placebo-controlled trials to alter the course of SSc-ILD (2)(3). While highlighting that SSc-ILD is treatable, the overall magnitude of the response to CYC in these studies was modest and the beneficial effects appeared to fade within a year after stopping treatment (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclophosphamide is the only therapy that has been shown in randomized controlled trials to have beneficial effects in the treatment of pulmonary fibrosis associated with connective tissue diseases (14,15). In the scleroderma lung study, treatment with oral cyclophosphamide at a dosage of Յ2 mg/kg/day for 12 months resulted in statistically significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In the 45 patient double blind placebo controlled study, there was a trend toward improved FVC in the cyclophosphamide group but this did not achieve statistical significance [48]. Thus, it remains unclear what the true role of IV cyclophophamide might be in the management of SSc related ILD.…”
Section: Cyclophosphamidementioning
confidence: 96%